Monitoring PHB production in Synechocystis sp. with hyperspectral images - Francisco Rodríguez Lorenzo; Miguel Placer Lorenzo; Luz Herrero Castilla; Juan Antonio Álvarez Rodríguez; Sandra Iglesias; Santiago Gómez; Juan Manuel Fernández Montenegro; Estel Rueda; Rubén Diez-Montero; Joan Garcia; Eva Gonzalez-Flo (Water Science and Technology, 2022)
Microalgae wastewater treatment systems have the potential for producing added-value products. More specifically, cyanobacteria are able to accumulate polyhydroxybutyrates (PHBs), which can be extracted and used for bioplastics production. Nonetheless, PHB production requires proper culture conditions and continue monitoring, challenging the state-of-the-art technologies. The aim of this study was to investigate the application of hyperspectral technologies to monitor cyanobacteria population growth and PHB production. We have established a ground-breaking measurement method able to discern spectral reflectance changes from light emitted to cyanobacteria in different phases. All in all, enabling to distinguish between cyanobacteria growth phase and PHB accumulation phase. Furthermore, first tests of classification algorithms used for machine learning and image recognition technologies had been applied to automatically recognize the different cyanobacteria species from a complex microbial community containing cyanobacteria and microalgae cultivated in pilot-scale photobioreactors (PBRs). We have defined three main indicators for monitoring PHB production: (i) cyanobacteria specific-strain density, (ii) differentiate between growth and PHB-accumulation and (iii) chlorosis progression. The results presented in this study represent an interesting alternative for traditional measurements in cyanobacteria PHB production and its application in pilot-scale PBRs. Although not directly determining the amount of PHB production, they would give insights on the undergoing processes. HIGHLIGHTS Hyperspectral technologies allow monitoring cyanobacteria population.; Spectral measurements differ between growth and PHB-accumulation phases.; Methodologies definition based on machine learning algorithms allowed on first approach to classify pilot-scale microorganisms and phases.; Image recognition algorithms permit a visual assessment of chlorosis advance.;